(untitled) (Linguostylistic Studies, 2023)
This article highlights grammatical features of Galyna Yastrubetska’s individual style. The main attention is paid to the establishment of semantic varieties of the object dependent on the predicate in the poetic works of the writer. Attention is focused on the semantic and syntactic structure of sentences. The expediency of applying the theory of syntactic dependencies in the analysis of the component composition of sentence constructions has been clarified. The object is analyzed as a predicate-dependent component of the sentence structure. The study has revealed that the main semantic variant of the dependent object component is the object of action, in which the semantic originality of the object category is most fully condensed. The dependent object of the action denotes the person /object to which the action is directed and is one of the central dependent components of the sentence. The main types of predicate components are action, process, and state predicates. The study findings argue that in the poetic texts of Galina Yastrubetska, the object dependent on the action predicate is most often used. It functions in the following sentence models: Sact + Pv(act) + О, Sact + Pv(act) + Оact + Adact, Sact + Pv(act) + Оact + Іac, Sact + Pv(act) + Оact + L1 + L2 + LЗ, Sact+ Pv (act) + Оact + Аdact + L1 + L2 + LЗ, Sact + Pv(act) + Оact + Аdact + Іmv + L1 + L2 + LЗ. There are also sentence constructions Sst + Padj(st) + Оst, Sst + Padv(st) + Оst with adjectival and adverbial predicates that condition the object of the state. There are 18 semantic groups representing the object dependent on the predicate. The dominant semantic groups are the groups of abstract vocabulary, lexemes denoting creatures, flora, fauna and commonly used vocabulary used for designating objects. Groups for the designation of creatures, flora, and fauna are differential.